Sistem Penunnjang Keputusan Pemilihan Pengajar Terbaik di SD Negeri Weetame dengan Metode Multi Atribute Decision Making - Yuliana Nale; Cecilia Dai Payon Binti Gabriel; Emirensiana Dapa Ege (International Forum of Researchers and Lecturers, 2025)
Teachers provide dedication to students to convey knowledge. In addition, teachers also play a role in educating, guiding, and training students so that they can understand the material being taught. Teachers have a very significant role in creating a superior and quality generation. The Principal at SDN Weetame does not utilize the application in the process of selecting qualified and competent teachers or instructors. Researchers observed and designed A selection support system for determining the best instructors implementing multi-attribute-based decision-making method, namely the WP (Weighted Product) method. The outcomes of this study reveal that SPK application can be used easily and produce decisions quickly so that the Principal can make the right choice.